Undergraduate students' adoption of handheld devices and Web 2.0 applications to supplement formal learning experiences: Case studies in Australia, Ethiopia and Malaysia. - Oliver, Beverley; Goerke, Veronica (International Journal of Education and Development using Information and Communication Technology, 2008)
This paper reports research into undergraduates’ adoption of handheld devices as supplementary learning tools. Students enrolled in Engineering and Business in Australia, Africa and Malaysia volunteered to participate in a study of their use of the HP iPAQ from mid-2005 to late-2006. The Business students were located in Perth (Australia) and in Addis Ababa (Ethiopia), and the Engineering students were located in Perth and Miri, Sarawak (Malaysia). Researchers observed and analysed the participants’ commencing levels of technology adoption, and then there subsequent adoption and perceptions of the usefulness of the iPAQ. Students did not recommend the iPAQ for learning because, using Roger’s reasons for adoption, it was trialable and observable but it failed to meet expectations. The Ethiopian students who, despite undeveloped ICT infrastructure, were most open to continue to experiment and persist with the device regardless of trying circumstances.